Production and bioprocessing of Taxol from Aspergillus niger, an endophyte of Encephalartos whitelockii, with a plausible biosynthetic stability: antiproliferative activity and cell cycle analysis - Gamal, Asmaa; Fikry, Eman; Tawfeek, Nora; El-Shafae, Azza M.; El-Sayed, Ashraf S. A.; El-Domiaty, Maher M. (Microbial Cell Factories, 2024)
The biosynthetic potency of Taxol by fungi raises their prospective to be a platform for commercial production of Taxol, nevertheless, the attenuation of its productivity with the fungal storage, is the challenge. Thus, screening for a novel fungal isolate inhabiting ethnopharmacological plants, with a plausible metabolic stability for Taxol production could be one of the most affordable approaches. Aspergillus niger OR414905.1, an endophyte of Encephalartos whitelockii, had the highest Taxol productivity (173.9 μg/L). The chemical identity of the purified Taxol was confirmed by HPLC, FTIR, and LC–MS/MS analyses, exhibiting the same molecular mass (854.5 m/z) and molecular fragmentation pattern of the authentic Taxol. The purified Taxol exhibited a potent antiproliferative activity against HepG-2, MCF-7 and Caco-2, with IC50 values 0.011, 0.016, and 0.067 μM, respectively, in addition to a significant activity against A. flavus, as a model of human fungal pathogen. The purified Taxol displayed a significant effect against the cellular migration of HepG-2 and MCF-7 cells, by ~ 52–59% after 72 h, compared to the control, confirming its interference with the cellular matrix formation. Furthermore, the purified Taxol exhibited a significant ability to prompt apoptosis in MCF-7 cells, by about 11-fold compared to control cells, suppressing their division at G2/M phase. Taxol productivity by A. niger has been optimized by the response surface methodology with Plackett–Burman Design and Central Composite Design, resulting in a remarkable ~ 1.6-fold increase (279.8 μg/L), over the control. The biological half-life time of Taxol productivity by A. niger was ~ 6 months of preservation at 4 ℃, however, the Taxol yield by A. niger was partially restored in response to ethyl acetate extracts of E. whitelockii, ensuring the presence of plant-derived signals that triggers the cryptic Taxol encoding genes.